Epitaxial Growth: Out‐Of‐Plane Metal Coordination for a True Solvent‐Free Building with Molecular Bricks: Dodging the Surface Ligand Effect for On‐Surface Vacuum Self‐Assembly (Adv. Funct. Mater. 20/2021). (17th May 2021) - Orbelli Biroli, Alessio; Calloni, Alberto; Bossi, Alberto; Jagadeesh, Madan S.; Albani, Guglielmo; Duò, Lamberto; Ciccacci, Franco; Goldoni, Andrea; Verdini, Alberto; Schio, Luca; Floreano, Luca; Bussetti, Gianlorenzo
Abstract : In article number 2011008, Alberto Bossi, Gianlorenzo Bussetti, and co‐workers present a coherent layered film grown on an archetypal Fe metal electrode. The ingredients for the controlled in‐vacuum self assembly are chemical decoupling of the contact interface, lateral (2D) ordering of the molecules, rigid molecule‐to‐molecule coupling along the third dimension and, sharp (chemical) termination of the layered film. (Graphic by Elisabetta Borseti; building: the new G. Feltrinelli Foundation headquarter in Milan is acknowledged).